Challenges for the Kasatoshi volcano hypothesis as the cause of a large return of sockeye salmon (Oncorhynchus nerka) to the Fraser River in 2010. (4th March 2013) - McKinnell, Skip
Abstract In August 2008 the Kasatoshi volcano in the Aleutian archipelago erupted. Prevailing winds carried volcanic ash to the Gulf of Alaska, where its soluble iron dissolved and initiated a widespread phytoplankton bloom. Two years later, the abundance of sockeye salmon (Oncorhynchus nerka) returning to spawn in the Fraser River was larger than any observed since 1913. Kasatoshi's influence on growth and survival has been proposed as the ultimate cause of the abundant return. However, when relevant data are brought to bear on the hypothesis, it shows that: (1) survival of the abundant sockeye salmon cohort was unremarkable when compared with the historical record; (2) without an accompanying volcano, survival of the returns in 2011 was about the same as in 2010; (3) parental abundance that spawned the abundant return in 2010 was the sixth largest since 1948; (4) during their first summer at sea, sockeye salmon are not known to migrate in the offshore region where the anomalous chlorophyll bloom occurred; (5) an older cohort that was likely exposed to the chlorophyll bloom had the second lowest productivity on record when it returned in 2009; (6) immature sockeye salmon do not feed on diatoms, so any trophodynamic benefit derived from excess chlorophyll in mid‐to late August 2008 would have to have found a rapid trophic pathway to sockeye salmon on the continental shelf; and (7) no other populations of sockeye salmon or other species of salmon that are known to rear in the same region had unexpectedly high returns.